PERSEPSI MASYARAKAT TERHADAP TANAMAN HIDROPONIK DI DESA LOTTA, KECAMATAN PINELENG, KABUPATEN MINAHASA - Stevanus G. Kaunang; Melsje Y. Memah; Ribka M. Kumaat (Sam Ratulangi University, 2016)
This study aimed to analyze and determine the public perception of hydroponic plant in the village Lotta, Pineleng Districts, views of the variables to be studied in terms of knowledge and personal characteristics and factors that, cultivation of hydroponic plants, seedlings, planting, remove seeds, caring for plants, harvesting, cleaning pipes, control water for circulation, plant nutrion, seed replacement, stimulus, personal factors, factors influence groups, cultural factors using a likert scale analysis tool. This aims was conducted over four months from February to the month of May 2016 from preparation to the arrangement of research reports. The location of research is Sentrum Agraris Lotta in the village Lotta districts Pineleng. This research uses primary data and secondary data. Primary data was obtained from 30 respondents using questionnaires, while secondary data obtained from the office Lotta village. The sampling method in this study is using purposive sampling method. The results of this study show that the public perception of plant hydroponic in the village Lotta districts Pineleng to categorize understand/agree as seen from the result obtained, that respondents will understand and know how to plant hydroponic and would like hydroponic plants.